2004
DOI: 10.1128/iai.72.11.6408-6417.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gonococcal Porin IB Activates NF-κB in Human Urethral Epithelium and Increases the Expression of Host Antiapoptotic Factors

Abstract: Infection of human urethral epithelial cells (UECs) with Neisseria gonorrhoeae increases the transcription of several host antiapoptotic genes, including bfl-1, cox-2, and c-IAP-2. In order to identify the bacterial factor(s) responsible for eliciting these changes, the transcriptional status of apoptotic machinery was monitored in UECs challenged with certain gonococcal membrane components. Initially, we observed that infection of UECs with gentamicin-killed gonococci increased the expression of the antiapopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 47 publications
(50 reference statements)
4
40
0
Order By: Relevance
“…We suggest that the VK2/ E6E7-specific dys-regulation of p53 is a potential mechanism that may be utilized by gonococci to keep the host cell alive despite DNA damage. This observation is consistent with the anti-apoptotic features of N. gonorrhoeae (Binnicker et al, 2004;Howie et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…We suggest that the VK2/ E6E7-specific dys-regulation of p53 is a potential mechanism that may be utilized by gonococci to keep the host cell alive despite DNA damage. This observation is consistent with the anti-apoptotic features of N. gonorrhoeae (Binnicker et al, 2004;Howie et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Diverse Bcl-2 family proteins have been found to play roles in the proapoptotic (39,40) and antiapoptotic (5,6,27,36) phenotypes observed upon N. gonorrhoeae infection in epithelial cells, but the extent to which individual Bcl-2 proteins act to mediate PMN survival has not been determined. A major regulator of neutrophil survival is thought to be the antiapoptotic Mcl-1 protein (1), whose role in inhibiting apoptosis in N. gonorrhoeae-infected PMNs remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have shown that human primary genital tract epithelial cells can serve as surfaces for gonococcal biofilm formation with minimal, if any, effect on cell viability. This may reflect the ability of the gonococcus to induce antiapoptotic factors in these cells (2,3).…”
Section: Discussionmentioning
confidence: 99%